1996
DOI: 10.1097/00005537-199606000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mitochondrial DNA Deletions and Cochlear Pathology: A Molecular Biologic Tool

Abstract: The purpose of these experiments was to develop a method of isolation, amplification, and identification of cochlear mitochondrial DNA (mtDNA) from minute quantities of tissue. Additionally, studies were designed to detect mtDNA deletions (mtDNA del) from the cochlea that previously have been amplified from other organ systems and tissues. MtDNA del have been associated with many pathologies, including neurological disorders, sensorineural hearing loss, ischemia, cardiomyopathies, and aging. DNA was extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…The acquired mitochondrial mutation that occurs most frequently in humans is the mitochondrial deletion mtDNA 4977 , which deletes 4977 bp between two 13-bp repeats starting at nucleotides 8470 and 13447. Analyses of human temporal bones indicated that mtDNA 4977 , the socalled 'common' deletion, occurred frequently in ARHI patients Dai, 2004], while it was almost absent in age-matched control patients without a history of ARHI [Seidman et al, 1996]. Similar analyses were conducted in rats, where a 4834-bp deletion was associated with ARHI and ageing in general .…”
Section: Do Mitochondrial Mutations and Reactive Oxygen Species Contrmentioning
confidence: 76%
“…The acquired mitochondrial mutation that occurs most frequently in humans is the mitochondrial deletion mtDNA 4977 , which deletes 4977 bp between two 13-bp repeats starting at nucleotides 8470 and 13447. Analyses of human temporal bones indicated that mtDNA 4977 , the socalled 'common' deletion, occurred frequently in ARHI patients Dai, 2004], while it was almost absent in age-matched control patients without a history of ARHI [Seidman et al, 1996]. Similar analyses were conducted in rats, where a 4834-bp deletion was associated with ARHI and ageing in general .…”
Section: Do Mitochondrial Mutations and Reactive Oxygen Species Contrmentioning
confidence: 76%
“…Cochlear and vestibular hair cells do not regenerate in humans; therefore, the maintenance and repair of these sensory structures is critical for maintaining cochlear and vestibular function with advancing age. Vascular changes in the cochlea and vestibular organs, including decreased vascular plasticity and permeability (Prazma et al 1990;Seidman et al 1996;Lyon and Wanamaker 1993;Gratton et al 1996), as well as decreased capillary diameter and blood flow (Lyon and Davis 2002) may compromise perfusion and result in reduced oxygen and nutrient delivery as well as reduced aerobic energy metabolism and increased ROM (McFadden et al 2001). ROMs are toxic molecules that can damage tissue and have been shown to damage mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Periods of confusion, elevated serum lactic acid levels around times of attacks, strokelike spells, magnetic resonance imaging (MRI) white matter signal changes, migrainelike headaches, seizures, diabetes, mitochondrial gene mutation (Mt-RNR1, Mt-TS1, POLG genes) 222,223 Other mitochondrial disorders Variable phenotypes 224 Bilateral synchronous internal auditory artery occlusion associated with vertebrobasilar vascular disease Vertigo, dysarthria, facial weakness, ataxia, nystagmus, unilateral numbness, abnormal computed tomography or magnetic resonance angiogram of the vertebrobasilar vasculature 48,50,[225][226][227] Cogan syndrome Nonsyphilitic interstitial keratitis of the cornea, hearing loss, vertigo 40 Neoplastic (neurofibromatosis II, bilateral vestibular schwannomas, intravascular lymphomatosis, others) Abnormal brain MRI or cerebrovascular imaging study [228][229][230] Sarcoidosis Pulmonary symptoms, bilateral vestibular loss, elevated serum angiotensin-converting enzyme level or abnormal Gallium scan 231,232 Hyperviscosity syndrome Mucous membrane bleeding, neurologic and pulmonary symptoms, associated retinopathy 233 carcinomatous meningitis, lymphomatous meningitis, and, very rarely, central nervous system (CNS) intravascular lymphomatosis and migrainous infarction. 59 Features that suggest multiple sclerosis would be unilateral weakness or numbness, visual loss, diplopia, or paraparesis.…”
Section: Table 5 Checklist Of Features Often Associated With Specifimentioning
confidence: 99%